Abnormal expression of miR-3653-3p, caspase 1, IL-1β in peripheral blood of schizophrenia - Zhao, Xin-ling; Liu, Yi-lin; Long, Qing; Zhang, Yun-qiao; You, Xu; Guo, Ze-yi; Cao, Xiang; Yu, Lei; Qin, Fu-yi; Teng, Zhao-wei; Zeng, Yong (BMC psychiatry, 2023)
Schizophrenia (SCZ) is a chronic, highly relapsing, severe mental disorder with an unclear etiology. Cytokine-mediated neuroimmune abnormalities have been repeatedly revealed. IL-1β was reported to play a vital role in expanding the inflammatory response. However, the underlying molecular mechanism is poorly understood. In this study, we found that miR-3653-3p with the NLRP3 binding site in Targetscan was differentially expressed in miRNA high-throughput sequencing in schizophrenia (SCZ), and indeed, its downregulation in SCZ peripheral blood was also verified by RT-qPCR ( P -value = 0.015). Furthermore, we found that the mRNAs of caspase 1 and IL-1β are elevated in people who suffer from SCZ ( P = 0.044 and P = 0.001, respectively). Moreover, the interaction of NLRP3, Caspase1, and IL-1β was found in the peripheral blood of patients with SCZ. The expression level of miR-3653-3p was negatively correlated with NLRP3 and IL-1β mRNA contents ( r = 0.487, P = 0.04 and r = 0.508, P = 0.037, respectively). NLRP3 mRNA was positively correlated with caspase1 mRNA. Meanwhile, the expression of miR-3653-3p was also negatively correlated with negative symptom subscores of PANSS ( r = 0.450, P = 0.046). IL-1β mRNA is positively correlated with the total scores of PANSS ( r = 0.690, P = 0.002) and the sub-scores of general psychopathology of PANSS ( r = 0.583, P = 0.014). Additionally, a significant positive relationship exists between IL-1β and the total duration ( r = 0.638, P = 0.006). We found that the combination of miR-3653-3p, caspase 1, and IL-1β have better diagnostic values. The results indicate that miR-3653-3p, caspase 1, and IL-1β can potentially be biomarkers of SCZ, identifying negative symptoms or a chronic course. A further understanding of the involvement of IL-1β in SCZ may be a crucial molecular effector for the chronic course to intervene.